The future of multiple sclerosis treatments - Coclitu, Catalina; Constantinescu, Cris S.; Tanasescu, Radu (Expert Reviews, 2016)
Introduction. There are not many conditions in which the last few decades have brought such a major change in the landscape of treatments as is the case of multiple sclerosis (MS). A number of disease modifying treatments (DMTs) are presently available for the treatment of the inflammatory phase of this disabling disease; however, the need for treating neurodegeneration and halting the progression of disability is still unmet.